Redundancy Features of Water Distribution Systems. (2017) - Di Nardo, A.; Di Natale, M.; Giudicianni, C.; Musmarra, D.; Varela, J.M. Rodriguez; Santonastaso, G.F.; Simone, A.; Tzatchkov, V.
Abstract: Water Distribution Systems (WDS) are traditionally built with topological and energy redundancy to improve network reliability against mechanical and hydraulic failure. This aim is achieved by designing them with many inter-connected closed loops and with pipe diameters that are larger than the ones strictly necessary to fulfil the design pressure at the network nodes. This general design approach, that lacks a systematic reliability based procedure, has been followed for decades in existing networks. Recently, novel topologic and energy metrics have been proposed for water distribution network analysis, design and partitioning. In this paper, four existing networks and two literature networks have been compared using several of these metrics trying to identify general features of this type of civil infrastructural networks. The comparison highlighted some network peculiarities, in terms of topology and energy, and, consequently, the possibility to define a range of similarity to build hypothetical benchmark networks. Further, the analysis highlighted that some correlations exist between topological and energy metrics although more studies are required.